GLORIA DEI AS A KEY TO UNDERSTAND CALVIN'S DOCTRINE OF PREDESTINATION - Billy Kristanto (STTRII, 2015)
This article analyses the doctrine of predestination in Calvin's thought and offers an alternative to understand it from the perspective of the glory of God. With historical and systematic theological argumentations, the writer offers a key thought for understanding the complexity of Calvin's doctrine of predestination. The idea of the glory of God can serve as a key to understand the doctrine.?